Orthogonal Experiments for Controlling the Formation of DBPs During Preozonation of Bromide-Containing Raw Water - 张怡然 王启山 王宏超 靳冲 李多 鲁金凤 (Transactions of Tianjin University, 2014)
Orthogonal method was adopted to optimize the preozonation process and to minimize the bromate formation. Factors such as contact time, pH and ammonia concentration were investigated by orthogonal experiments to understand the interaction of various operation conditions on the formation of bromate and other disinfection byproducts （DBPs）. Results showed that pH had the most significant influence on the minimization of bromate formation. The factors influencing the formation ofbromate were in order ofpH 〉 contact time 〉 ammonia concentration. For the formation of trihalomethanes （THMs） and haloacetic acids （HAAs）, however, contact time significantly influenced their formation potential. In the practical preozonation process of waterworks, it is appropriate to set preozonation contact time to be 20 min. In order to minimize the formation of bromate, pH value of the raw water should be adjusted to 6.0, and a certain concentration of ammonia could be added into the water to strengthen the minimization effect when the concentration of bromide in the raw water is higher than that in the experimental water.